2017
DOI: 10.1108/arla-10-2015-0275
|View full text |Cite
|
Sign up to set email alerts
|

Is organizational learning culture a good bet?

Abstract: Purpose Interest in the relationship between organizational culture and performance is not new but it still attracts considerable attention from researchers. In the literature on organizational learning, organizational culture is mainly conceived as an essential condition to facilitate and support learning and consequently as an important feature in achieving organizational performance nowadays. In the scope of this research topic, the purpose of this paper is to analyze the effect of organizational learning c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Besides, organizational learning is a default knowledge for all employees in an organization. In the same vein, researchers confirmed that the organizational learning is linked to organizational culture in a "both-ways" relation (Abbasi and Zamani-Miandashti 2013; Pantouvakis and Bouranta 2013; Rebelo et al 2017). We know that organizational learning relies on motivation based on the existing literature; therefore, we believe that robust organizational learning may support the constant search for service innovation.…”
Section: Managerial Implicationsmentioning
confidence: 66%
See 2 more Smart Citations
“…Besides, organizational learning is a default knowledge for all employees in an organization. In the same vein, researchers confirmed that the organizational learning is linked to organizational culture in a "both-ways" relation (Abbasi and Zamani-Miandashti 2013; Pantouvakis and Bouranta 2013; Rebelo et al 2017). We know that organizational learning relies on motivation based on the existing literature; therefore, we believe that robust organizational learning may support the constant search for service innovation.…”
Section: Managerial Implicationsmentioning
confidence: 66%
“…Secondly, we recognized that organizational learning is another crucial variable in connecting internal marketing and service innovation. Following the first variable, the organizational learning also appeared between 1990 and 2017 in internal marketing and service innovation research (Cui et al 2013;Gupta and Rogers 1991;Hassan and Foltz 1990;Kahn and Mentzer 1998;Kearns and Lederer 2003;Lings 1999;Pantouvakis and Bouranta 2013;Rebelo et al 2017;Sundbo and Gallouj 2000). According to them, organizational learning helps the employee to understand the organization functions as a default knowledge while working at a company, and it is deeply related to innovation as it defines the way that the knowledge acquired from internal and external sources flows inside the organization.…”
Section: Regarding Potential Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The rituals (celebrations, communications, rules, etc.) that reinforce such ideas, assumptions, and values appear as the organization's and its leadership's perceived values (Rebelo & Gomes, 2017). The shared goals, common behaviours, joint attitudes, and patterns of meaning that guide the activities of an organization's or community's members are framed by the culture of the organisation or community.…”
Section: Organisational Culturementioning
confidence: 99%
“…This indicated that more empirical analysis was still needed to design future guides for promoting effective innovation. Moreover, OLC promotes and facilitates workers learning, sharing and dissemination of information regarding the achievement of organizational goals (Rebelo & Gomes, 2017). This was rooted based on Schein (1992), where OLC was defined as the behaviors and beliefs derived from deep generational basic assumptions, because of its ability to solve internal and external problems with internal consistency and external adaptability, respectively.…”
Section: Introductionmentioning
confidence: 99%